Historical essay of creation and functioning of the Ministry of Railways of the Russian empire - A. Yu. Bilyk (History of science and technology, 2013)
The article covers history of creation and functioning of the Ministry of Railways of the Russian Empire. Almost all subdivisions of the Ministry are characterized, the aims and tasks of its activity are noted. The scientific achievements are considered, the scientific journals, which appeared under the auspices of the Ministry, are characterized. The role of scientific and technical journals of this establishment in scientific researches and propaganda of scientific and technical knowledge is emphasized.